(untitled) (Balthazar, 2023)
In this paper, I propose a Kantian argument to justify the necessity of the cultivation of empathy and the morally relevant role it can play for the agent once cultivated. Indeed, by referring to the Kant’s works, it is possible to show that empathy is a feeling inherent in human nature that guides the agent in the process of moral deliberation. Nevertheless, it cannot directly determine the agent’s will, but must be critically evaluated by practical reason. The latter, however, does not merely sift sentiment; it can, and must, cultivate empathy. Empathy cultivated by practical reason plays two morally relevant roles in the morality of action and the constitution of moral character: a motivational role and an epistemic one. Finally, I show how Kant’s conception of the process of evaluation and cultivation of feeling can enrich the debate not only on the necessity of emotion regulation, but also on the regulation techniques that can be employed.